Modeling and Bio-economic analysis of broilers’ performance in Benin - HOUNDONOUGBO, M. FRÉDÉRIC; CHWALIBOG, André; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI (My University, 2009)
The objective of this paper was to model bio-economic variables in broilers feeding. During 7 weeks, 120 broilers Red Bro were fed with diets containing soybean meals from solvent (Ss) or expeller (Se) processing. At grower phase (d 22 to d 49) the diets were switched for half of broilers in each treatment. The General Linear Model (model I) and Mixed Procedure (model II) were used to analyze data in SAS (2004). In model I no significant effect (P > 0.05) of diet was found on the daily feed intake (DFI) and the daily body weight gain (DWG) at both phases, but the starter diet affect significantly the feed conversion ratio (FCR), the feed cost (FC) and the economic feed efficiency (EFE). The model II showed that at starter phase the interaction between diet and age had a significant effect on DFI, DWG, FCR, FC and EFE. At grower phase, there was no interaction effect. The age affected significantly DFI and DWG, while the diet had significant effect on FCR, FC and EFE. The switch of diets resulted in a compensatory growth of broilers fed Se diet previously. At the grower phase the daily feed intake and body weight were fitted by polynomial curve functions with the age as main explanatory variable. (RASPA, 7 (S) : 93-98).
Keywords: Broilers - Economic feed efficiency - Feed cost- Polynomial functions - Soybean meals.